Effect of reducing agents types - on the synthesis of silver nanoparticles - Noor Asyida, Mohamed (2014)
In recent years, metal nanoparticles such as silver have been studied extensively due to their unique properties that are significantly different from those of bulk material. In this study, silver nanoparticles were synthesized by chemical reduction method with different type and concentration of reducing agents which is glucose and Cetyl trimethylammonium bromide (CTAB). The effect of the reducing agent on the size and morphology of the silver nanoparticles has been investigated. In this study, the formation and morphology of nanosized silver nanoparticles has been characterized by using UV-VIS spectroscopy, and Field Emission Scanning Electron Microscopy analysis (FESEM), respectively. Meanwhile, the purity of element on the synthesized silver nanoparticles has been carried out by Energy-dispersive X-ray spectroscopy (EDX). From the results of UV-Vis, silver nanoparticles that used glucose as a reducing agent showed narrow size distribution compared to CTAB. The maximum absorbance of silver nanoparticles for glucose as reducing agent is 0.481 while for CTAB is 0.831. The average size of the resulting silver nanoparticles for the concentration were determined by Image J software and result for the size is 10 nm with the high purity (91.95 % weight) using glucose and (77.78 % weight) when used CTAB as a reducing agents. During sample preparation, glucose showed a slow reaction as reducing agents compare with CTAB, which is more suitable to control a size and morphology of silver nanoparticles. The synthesis of silver nanoparticles has remains a formidable challenge in order to find a simple way to generate monodisperse silver nanoparticles with small size at high concentration.